SEARCH OF TRACES OF GEOPHYSICAL PHENOMENA IN SERIES OF LATITUDE DETERMINATIONS ON PRISMATIC ASTROLABE IN POLTAVA - Zalivadnyi, N. M.; Khalyavina, L. Ya.; Borisyuk, T. Ye. (Одеські астрономічні публікації, 2007)
The influences of some geophysical phenomena on the long-term observation results which are obtained in Poltava with prismatic astolabe, are have been studied. It is established: 1) the non-polar variations of latitude reveals global cycles, typical for uniform system the Ears - the ocean - the atmosphere; 2) the correlation degree between non-polar zenith shifts and Solar activity index in media-term region (6-12 years) of spectrum is very high.